The Influence of Financial Technology on Financial Performance Moderated by Internet Financial Reporting in Indonesia - Moh. Rizal Syafiie; Ilham Wahyudi; Rita Friyani (Indonesian Journal of Business Analytics, 2024)
It is hoped that the presence of fintech can be relied on to improve financial performance such as increasing profitability, reducing operational costs and overcoming credit problems. However, in reality the financial performance of fintech companies is still not optimal. This research aims to ensure that companies can continue to improve their financial performance and to determine the importance of fintech and digital financial services in the economy. This research method uses a quantitative approach. The population of this research are companies listed on the Indonesia Stock Exchange (BEI) which are included in the list of Financial Technology Companies. The data was processed using IBM SPSS version 22 software. The research results show that financial technology is able to improve financial performance and Internet Financial Reporting (IFR) is able to moderate the relationship between financial technology and financial performance in fintech companies listed on the Indonesia Stock Exchange (BEI) in 2018 - 2021.